ANALYTICAL VALIDATION AND REFERENCE INTERVAL VERIFICATION OF PLASMA APOLIPOPROTEIN B QUANTIFICATION IN ADULTS AGED 41-60 YEARS (Vietnam Journal of Community Medicine, 2026)
Objective: To validate the analytical performance (precision, trueness, linearity) and verify the reference interval of plasma apolipoprotein B quantification on the Cobas® C501 analyzer at Xuyen A General Hospital for adults aged 41-60 years.Methods: Analytical validation followed CLSI EP15-A3 and EP06 guidelines, applying biological variation criteria (TEa = 11.6%, EFLM database). Reference interval verification followed CLSI EP28-A3c using an outlier-counting approach (acceptance threshold ≤ 10%) in 66 healthy individuals (25 males, 41 females) aged 41-60 years.Results: The assay met all acceptance criteria for precision (CVR: 0.92-0.98%, limit ≤ 2.90%, CVWL: 1.01-1.59%, limit ≤ 3.83%), trueness (%Bias: 1.64-1.71%, limit ≤ 5.80%), and linearity (R = 1.0000, slope = 1.0171; range 19.33-165.00 mg/dL). The manufacturer’s reference intervals were verified as suitable: 0/24 male samples fell outside 66-144 mg/dL, and 2/41 female samples (4.9%) fell outside 60-141 mg/dL, both within the acceptance threshold.Conclusion: The apolipoprotein B assay on Cobas® C501 demonstrates reliable analytical performance meeting biological variation-based criteria. The manufacturer’s reference intervals are appropriate for the 41-60 age group at this institution, providing the scientific and regulatory basis for routine clinical implementation.
Keywords: Apolipoprotein B, analytical validation, reference interval verification, biological variation, Cobas C501.